2011
DOI: 10.1089/cmb.2010.0215
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Control Model Reveals Systematic Feedback and Key Molecules in Metabolic Pathway Regulation

Abstract: Robust behavior in metabolic pathways resembles stabilized performance in systems under autonomous control. This suggests we can apply control theory to study existing regulation in these cellular networks. Here, we use model-reference adaptive control (MRAC) to investigate the dynamics of de novo sphingolipid synthesis regulation in a combined theoretical and experimental case study. The effects of serine palmitoyltransferase over-expression on this pathway are studied in vitro using human embryonic kidney ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This report extends previous work that demonstrated the original use of MRAC to infer potential regulatory interactions [5]. Specifically, we (a) assess the efficacy and robustness of the proposed controller using MRAC in terms of tracking error, i.e., how closely the plant dynamics follow the reference dynamics, and (b) interpret the control and feedback dynamics in the context of relevant literature for potential insight into sphingolipid de novo synthesis pathway regulation.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This report extends previous work that demonstrated the original use of MRAC to infer potential regulatory interactions [5]. Specifically, we (a) assess the efficacy and robustness of the proposed controller using MRAC in terms of tracking error, i.e., how closely the plant dynamics follow the reference dynamics, and (b) interpret the control and feedback dynamics in the context of relevant literature for potential insight into sphingolipid de novo synthesis pathway regulation.…”
Section: Introductionsupporting
confidence: 59%
“…where k a,b indicates the rate constant for the reaction from a to b (see [5] for details of other pathway reactions). Rate constants are estimated using data from the C 16 dual-chain labeled species.…”
Section: Methodsmentioning
confidence: 99%
“…One used model-reference adaptive control (MRAC) to investigate the dynamics of de novo sphingolipid synthesis by Hek cells stably transfected with serine palmitoyltransferase, and the MRAC simulations produced results that were comparable to simulations from a standard model using mass action kinetics, and suggested that there might be adaptive feedback from increased metabolite levels. ( 638 ) The other approach integrated lipidomics and transcriptomics data collected by the LIPID MAPS Consortium ( ) for RAW264.7 cells using a two-step matrix-based approach wherein the rate constants obtained from the first step were further refined using generalized constrained nonlinear optimization. ( 639 ) The primary focus of the analysis was the C16-ceramide backbone species, and the resulting model fit the experimental data, with the robustness of the model being validated through parametric sensitivity analysis.…”
Section: Integration Of “Omic” Data Sets For a Systems Biology Of Sphmentioning
confidence: 99%
“…Two other mathematical approaches have been applied to data sets from studies of mammalian sphingolipid biosynthesis. One used model-reference adaptive control (MRAC) to investigate the dynamics of de novo sphingolipid synthesis by Hek cells stably transfected with serine palmitoyltransferase, and the MRAC simulations produced results that were comparable to simulations from a standard model using mass action kinetics, and suggested that there might be adaptive feedback from increased metabolite levels . The other approach integrated lipidomics and transcriptomics data collected by the LIPID MAPS Consortium () for RAW264.7 cells using a two-step matrix-based approach wherein the rate constants obtained from the first step were further refined using generalized constrained nonlinear optimization .…”
Section: Integration Of “Omic” Data Sets For a Systems Biology Of Sph...mentioning
confidence: 99%
“…Using this technique they expanded on a previous single-scale model and were able to decouple the promigratory and anti-proliferative effects of TGF-β1 on various cell types in an in silico skin wound closure model over time. Analogous reasoning and techniques are also used for analysis of metabolic and signaling networks in which a steady state flux is desired for informing higher tiers of function (3, 5, 6, 45, 48). …”
Section: Current Multiscale Modeling Effortsmentioning
confidence: 99%